Implementasi Kebijakan Penurunan Stunting di Siempat Nempu Hulu (Analisis Intervensi Gizi Spesifik dan Sensitif) - Shofiyah Muannis Simanullang; Donal Nababan; Lia Rosa Sinaga; Agnes Purba; Laura Siregar (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Stunting is a chronic nutritional problem that affects the quality of human resources and remains a major public health challenge in Indonesia, including Dairi Regency, which has a prevalence of 28.6%. In Siempat Nempu Hulu Subdistrict, the prevalence increased from 15.36% in 2022 to 21.17% in 2023, indicating that the implementation of stunting reduction policies has not been optimal. This study aims to analyze the implementation of stunting reduction policies through specific and sensitive nutrition interventions. This research used a qualitative approach with a case study design. Eight informants were selected purposively, comprising health office officials, health workers, village officials, posyandu cadres, and families with children under five. Data were collected through in-depth interviews, observation, and document analysis, and the data were analyzed thematically based on Edward III’s policy implementation theory, which includes communication, resources, implementers’ disposition, and bureaucratic structure. The results showed that inter-institutional communication was well established but not fully effective at the community level. Resources were available but not optimally utilized, implementers showed good commitment, and the bureaucratic structure was established but still faced coordination and socio-economic challenges. It is concluded that policy implementation has not been optimal, thus requiring strengthened communication, community empowerment, and improved resource utilization.